1983
DOI: 10.1002/macp.1983.021840212
|View full text |Cite
|
Sign up to set email alerts
|

Study of step‐growth polymerizations using epoxy‐carboxy reaction, 4. Study of the epoxy‐carboxy reaction carried out in the melt on high molecular weight models

Abstract: Epoxy-carboxy polycondensation is studied in the melt by use of the octadecanoic acid11 -dodecyloxy-2,3-epoxypropane reaction as a model. The catalyst is N,N-dimethyldodecylamine. The results obtained from these high molecular weight models show that, as for the studies performed in a solvent, two main reactions take place. The experiments are carried out under stoichiometric and non-stoichiometric conditions. It appears that, due to the strong interaction between epoxy compound and amine, a polymerization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…A solvent extraction method was used to separate PS- g -PBT copolymers from blend constituents of PBT and PS. The specimen prepared by either SOM or MB was dissolved into a mixed solvent of phenol and OCB (50/50 v/v) at 50 °C for 2 h. Madec and Marechal reported that the noncatalyzed reaction rate constant, k , of octadecanoic acid and 1-dodecyloxy-2,3-epoxy propane in OCB at 121 °C is 4.2 × 10 -6 kg mol -1 s -1 . Therefore, very little, if any, reaction occurred between the unreacted PBT and PS-GMA in phenol/OCB at 50 °C.…”
Section: Methodsmentioning
confidence: 99%
“…A solvent extraction method was used to separate PS- g -PBT copolymers from blend constituents of PBT and PS. The specimen prepared by either SOM or MB was dissolved into a mixed solvent of phenol and OCB (50/50 v/v) at 50 °C for 2 h. Madec and Marechal reported that the noncatalyzed reaction rate constant, k , of octadecanoic acid and 1-dodecyloxy-2,3-epoxy propane in OCB at 121 °C is 4.2 × 10 -6 kg mol -1 s -1 . Therefore, very little, if any, reaction occurred between the unreacted PBT and PS-GMA in phenol/OCB at 50 °C.…”
Section: Methodsmentioning
confidence: 99%
“…28 Based on previous studies, [29][30][31][32] the possible interactions between ELO, DCAs and DMAP are proposed as shown in Scheme 1. 28 Based on previous studies, [29][30][31][32] the possible interactions between ELO, DCAs and DMAP are proposed as shown in Scheme 1.…”
Section: Ft-ir Analysismentioning
confidence: 99%
“…Several alternative synthetic strategies such as creation of the molecular asymmetry by incorporating of noncoplanar groups in the main chain, attaching the bulky pendant groups, for instance, the introduction of substituents (alkyl or alkoxy groups) in the ortho-position of the aromatic ring or insertion of aliphatic flexible spacers between aromatic rings within the main chain are approached. 18 Siloxane moiety had also inserted as a flexible spacer, either in the amine or carbonyl component, resulting in polyazomethines with improved solubility [19][20][21][22][23][24][25] because of high flexibility of the siloxane bond and weak intermolecular interactions between dimethylsiloxane units. 4,17 The inclusion of polyazomethines in rotaxane architecture is another strategy approached to improve their processability.…”
Section: Introductionmentioning
confidence: 99%
“…4,17 The inclusion of polyazomethines in rotaxane architecture is another strategy approached to improve their processability. 18 Siloxane moiety had also inserted as a flexible spacer, either in the amine or carbonyl component, resulting in polyazomethines with improved solubility [19][20][21][22][23][24][25] because of high flexibility of the siloxane bond and weak intermolecular interactions between dimethylsiloxane units.…”
Section: Introductionmentioning
confidence: 99%